2016
DOI: 10.1007/s10853-016-9739-4
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of self-setting composites: influence of the carboxymethylcellulose content and hydration state

Abstract: OATAO is an open access repository that collects the work of Toulouse researchers and makes it freely available over the web where possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…As either oil or shortening increased, wear rate increased for all formulations. This was likely because increased lipids levels would increase malleability and reduced rigidity (Jacquart et al., ), as seen in the strain sweep and frequency sweep results.…”
Section: Resultsmentioning
confidence: 95%
“…As either oil or shortening increased, wear rate increased for all formulations. This was likely because increased lipids levels would increase malleability and reduced rigidity (Jacquart et al., ), as seen in the strain sweep and frequency sweep results.…”
Section: Resultsmentioning
confidence: 95%
“…The significant influence of TTCP/DCPA ratio on the CS of PAA cements due to cross-linking PAA via Ca ions was measured [ 57 ]. On the other side, the rise in addition of CMC to the brushite/vaterite cement up to 50 wt% caused the increase in dry composite CS to 86 MPa as a result of cement porosity reduction [ 58 ]. The injectability (and cohesion) of αTCP cement was improved by 1.5 wt% addition of CMC up to 90% while the setting time decreased from 11 to 7 min [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sprio et al, showed that the addition of sodium alginate to the cement-based on the Sr-substituted α-TCP led to an increase in the compressive strength and this was attributed to a crack-bridging effect J o u r n a l P r e -p r o o f 33 provided by alginate [24]. It has been reported by Jacquart et al, that the use of carboxymethylcellulose with DCPD-CaCO3 cement significantly enhanced the compressive strength of formulated composites [51]. The use of sodium phosphate solution for the preparation of alginate gel resulted in an increase of compressive strength of cements formulated with BGc and BGm (CPC-BGc-Alg-NaP and CPC-BGm-Alg-NaP).…”
Section: Compressive Strengthmentioning
confidence: 90%